Pemanfaatan bahan makanan lokal kentang (Solanum tuberosum l), ikan lele (Clarias, sp) dan brokoli (Brassica oleracea l) dalam bentuk snack kroket untuk balita dengan status gizi kronis - Niken Yunia Rifqi; Sugeng Iwan; Nurul Hakimah (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
The percentage of children under five in RW 2 with the characteristics of chronic nutritional status is 8 people or 73%. Chronic indicators describe the nutritional problems of children under five in the long term, due to low BW/U index, short BW/U, normal BW/TB. The purpose of this study was to determine the nutritional quality, protein quality of the formula. knowing the best treatment, organoleptic quality of the formula for the use of local food ingredients: potato (Solanum tuberosum L), catfish (Clarias Sp), and broccoli (Brassica oleracea L). This type of research is experimental with a completely randomized design (CRD). The level of treatment was the ratio of potato: catfish: broccoli, namely P1 (40:30:30), and P2 (30:45:25). The croquette snack formula at treatment levels 1 and 2 had nutritional values, namely energy of 156 Kcal and 125 Kcal. The value of P1 protein is 7.6 grams, P2 is 8.85 grams, P1 fat is 6.36 grams and P2 is 2.76 grams. Nutritional content in P1 is better than P2 seen from the calculation of nutritional value and protein quality. The digestibility quality of P1 was higher at 94.4. The level of treatment P1 (40:30:30) was the best treatment level in terms of the number of Nh, which was 0.53. Organoleptic quality at P1 was preferred by panelists for the attributes of color, taste, texture, and aroma of potato croquettes, which obtained an average value on a scale of 3. This study concluded that the addition of catfish increased the protein and phosphorus content in the croquette formula. The addition of broccoli increases the content of vitamin C and phosphorus. P1 nutritional quality (energy, protein, fat, carbohydrates). The best treatment is treatment 1 with a higher value than treatment 2 and the organoleptic quality of the P1 formula is preferred by the panelists than P2.